Radiofrequency ablation compared with laparoscopic adrenalectomy for aldosterone‐producing adenoma. Issue 11 (11th August 2016) - Liu, S. Y.; Chu, C. M.; Kong, A. P.; Wong, S. K.; Chiu, P. W.; Chow, F. C.; Ng, E. K.
Abstract: Background: Radiofrequency ablation (RFA) is an emerging treatment for primary aldosteronism owing to aldosterone‐producing adenoma. Whether RFA could be an alternative treatment to laparoscopic adrenalectomy is unknown. Methods: This was a retrospective comparative study in patients with aldosterone‐producing adenoma undergoing either laparoscopic adrenalectomy or CT‐guided percutaneous RFA between 2004 and 2012. Short‐term outcomes and long‐term resolution rates of primary aldosteronism (normalized aldosterone to renin ratio), hypokalaemia and hypertension (BP lower than 140/90 mmHg without antihypertensive medical therapy) were evaluated. Results: Some 63 patients were included, 27 in the laparoscopic adrenalectomy group and 36 in the RFA group. RFA was associated with shorter duration of operation (median 12 versus 124 min; P  < 0·001), shorter hospital stay (2 versus 4 days; P  < 0·001), lower analgesic requirements (13 of 36 versus 23 of 27 patients; P  < 0·001) and earlier resumption of work (median 4 versus 14 days; P  = 0·006). Morbidity rates were similar in the two groups. With median follow‐up of 5·7 (range 1·9–10·6) years, resolution of primary aldosteronism was seen in 33 of 36 patients treated with RFA and all 27 patients who had laparoscopic adrenalectomy ( P  = 0·180). Hypertension was resolved less frequently after treatment with RFA compared with laparoscopic adrenalectomy (13 of 36 versus 19 of 27 patients; P  = 0·007). Hypokalaemia was resolved in all patients. Conclusion: For patients with aldosterone‐producing adenoma the efficacy of resolution of primary aldosteronism and hypertension was inferior after treatment with RFA compared with laparoscopic adrenalectomy. Abstract : Radiofrequency ablation was inferior to surgery